c.2 - Dreze, Jean; Sen, Amartya (New Delhi, 2002)
This book explores the role of public action in eliminating deprivation and expanding human freedoms in India. The analysis is based on a broad and integrated view of development, which focuses on well-being and freedom rather than the standard indicators of economic growth. The authors place human agency at the centre of stage, and stress the complementary roles of different institutions (economic, social and political) in enhancing effective freedoms.
Keywords: Economic development - India